THE SYSTEMATIC REVIEW OF THE COMPLICATIONS AND OUTCOMES OF POST PEDIATRIC CRANIOPLASTY - Steven; Oktavia, Jessica; Irene; Wahyudi, Irawan (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Difficulties from cranioplasty are normal in pediatric patients. Be that as it may, insights on cranioplasty procedures, intricacies, and long haul impacts are not surely known. This study does an extensive writing survey to give an outline of current cranioplasty rehearses in youngsters. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed and SCIENCE DIRECT, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 100 articles, whereas the results of our search on SCIENCE DIRECT brought up 417 articles. The results of the search conducted for the last year of 2014 yielded a total 17 articles for PubMed and 7 articles for SCIENCE DIRECT. In the end, we compiled a total of 5 papers, 3 of which came from PubMed and 2 of which came from SCIENCE DIRECT. We included five research that met the criteria. Conclusion: In summary, the complications for carnioplasty are quite common. Furthermore, the present research lacks well-documented and comparable outcome factors, implying that prospective, long-term multicenter cohort studies are required to optimize cranioplasty procedures in children who will undergo cranioplasty following craniectomy.